PERENCANAAN DAN STRATEGI PEMBANGUNAN DI INDONESIA - Wibowo, Edi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2008)
ABSTRACT Policy of national development has very strategic and important function and role to attainment of target national development. The successful of national development do not only determined by governmental role, but also having to support by role of private sector and society to development stakeholders. Important role differ from people economics is in absorption of labor. Problem lacking of capital faced by Indonesia, can be solved with solid investment pattern of labor, because can create the more business unit as well as opportunity of job, so that can solve problem unemployment. Keywords: unemployment, economic planning, economic development, national development